THE INFLUENCE OF BRAND IMAGE, AND SHARIA BUSINESS ETHICS ON CUSTOMER LOYALTY IN SHARIA BANKS - Sri Wahyuni; Lisya Amanda (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study is motivated by the relatively low level of customer loyalty toward Islamic banks in Medan City, despite continuous efforts to strengthen brand image and the implementation of Islamic business ethics. This phenomenon indicates a gap between the positive image promoted by Islamic banks and the actual experiences perceived by customers. The purpose of this research is to analyze the influence of Brand Image and Islamic Business Ethics on Customer Loyalty in Islamic banking among the community of Medan City. This research employed a quantitative approach using a survey method, with data collected through an online questionnaire (Google Form) distributed to customers of Islamic banks. All variables were measured using a five-point Likert scale, and data were analyzed using the SmartPLS (Partial Least Squares) application to test validity, reliability, and the causal relationships among variables. The results show that all indicators of the research variables are valid and reliable. Structurally, Brand Image has a significant but negative effect on Customer Loyalty, indicating that a stronger brand image does not necessarily enhance customer loyalty. Meanwhile, Islamic Business Ethics has a positive but not significant effect on Customer Loyalty. These findings suggest that customer loyalty toward Islamic banks in Medan is more influenced by direct service experiences rather than by perceived image and ethical values.